(untitled) (Research, Society and Development, 2021)
The speech therapist in Home care works by managing the needs of patients, such as, for example, in dysphagia, performing continuous evaluations, in addition to specifying the most appropriate methods of treatment. The general objective of this research is to analyze the importance of the performance of the speech therapist in the home environment. Among the specific objectives, the following stand out: to identify the role of the speech therapist in home care; verify the benefits to the patient in carrying out the treatment at home; demonstrate what are the main demands of the speech therapist in home care. The research problem lies in the following question: what is the importance of speech therapy in patients’ homes? Regarding the methodology, the research can be characterized as a bibliographic review of the integrative type, of qualitative analysis, aiming at the systematization of results from varied theoretical sources on the present theme, especially articles available in databases directed to research scientific, such as Scielo, Capes, Scholar. It was evidenced through the studies found that the speech therapist is of paramount importance for personalized care, as it provides a reduction in the risks of hospitalizations, thus avoiding exposures to the hospital environment, with the privacy of the family bed, facilitating treatment, because emotional support is of fundamental importance for recovery.